In‐plane ultrasonic needle tracking using a fiber‐optic hydrophone. Issue 10 (22nd September 2015) - Xia, Wenfeng; Mari, Jean Martial; West, Simeon J.; Ginsberg, Yuval; David, Anna L.; Ourselin, Sebastien; Desjardins, Adrien E.
Abstract : Purpose: Accurate and efficient guidance of needles to procedural targets is critically important during percutaneous interventional procedures. Ultrasound imaging is widely used for real‐time image guidance in a variety of clinical contexts, but with this modality, uncertainties about the location of the needle tip within the image plane lead to significant complications. Whilst several methods have been proposed to improve the visibility of the needle, achieving accuracy and compatibility with current clinical practice is an ongoing challenge. In this paper, the authors present a method for directly visualizing the needle tip using an integrated fiber‐optic ultrasound receiver in conjunction with the imaging probe used to acquire B‐mode ultrasound images. Methods: Needle visualization and ultrasound imaging were performed with a clinical ultrasound imaging system. A miniature fiber‐optic ultrasound hydrophone was integrated into a 20 gauge injection needle tip to receive transmissions from individual transducer elements of the ultrasound imaging probe. The received signals were reconstructed to create an image of the needle tip. Ultrasound B‐mode imaging was interleaved with needle tip imaging. A first set of measurements was acquired in water and tissue ex vivo with a wide range of insertion angles (15°–68°) to study the accuracy and sensitivity of the tracking method. A second set was acquired in an in vivo swine model, with needle insertions to the brachial plexus. A third set was acquired in an in vivo ovine model for fetal interventions, with insertions to different locations within the uterine cavity. Two linear ultrasound imaging probes were used: a 14–5 MHz probe for the first and second sets, and a 9–4 MHz probe for the third. Results: During insertions in tissue ex vivo and in vivo, the imaged needle tip had submillimeter axial and lateral dimensions. The signal‐to‐noise (SNR) of the needle tip was found to depend on the insertion angle. With the needle tip in water, the SNR of the needle tip varied with insertion angle, attaining values of 284 at 27° and 501 at 68°. In swine tissue ex vivo, the SNR decreased from 80 at 15° to 16 at 61°. In swine tissue in vivo, the SNR varied with depth, from 200 at 17.5 mm to 48 at 26 mm, with a constant insertion angle of 40°. In ovine tissue in vivo, within the uterine cavity, the SNR varied from 46.4 at 25 mm depth to 18.4 at 32 mm depth, with insertion angles in the range of 26°–65°. Conclusions: A fiber‐optic ultrasound receiver integrated into the needle cannula in combination with single‐element transmissions from the imaging probe allows for direct visualization of the needle tip within the ultrasound imaging plane. Visualization of the needle tip was achieved at depths and insertion angles that are encountered during nerve blocks and fetal interventions. The method presented in this paper has strong potential to improve the safety and efficiency of ultrasound‐guided needle insertions.